Lematización para palabras médicas complejas: Implementación de un algoritmo en LISP. - PEINADO RODRIGUEZ, Jesús (Revista Médica Herediana, 2013)
The automated retrieval of files depends critically on the ability to generate precise signs concepts. Stemming is a technique very useful but medical terms are very complex terms which need special attention. Our main was to develop a modular algorithm for complex medical terms in order to follow a new space of research on Information retrieval. The algorithm was developed using LISP, a programming language, and exhaustive controlled list of rules. As a result, we found good precision with less recall when we asked for concepts saving signs concepts for each medical term. (Rev Hed Hered 2003; 14:224-229).